INTEGRATING LOCAL WISDOM IN CHARACTER EDUCATION: A PROJECT-BASED APPROACH IN THE MERDEKA CURRICULUM - Prasetya, Muhammad Novan; Anis Munfarikhatin (Nusantara Hasana Journal, 2025)
This study aims to develop teaching modules within the Merdeka Curriculum that integrate the character values of patriotism with local wisdom in Merauke. In the rapid globalization era, it is crucial to strengthen students' love for their country through education relevant to their cultural context. The developed teaching modules incorporate local wisdom values such as mutual cooperation (gotong royong), diversity, and respect for nature to instill a sense of nationalism and a strong cultural identity. The research methodology includes needs analysis, module design, trials, and evaluation. The results show that the developed teaching modules effectively enhance students' understanding of patriotism and appreciation for local culture. The implementation of these modules is expected to be an initial step toward supporting holistic and contextual character education in South Papua, as well as a model that can be adapted in other regions with different local wisdom.